KESALAHAN KONSEP DALAM PEMBELAJARAN SAINS DI MADRASAH IBTIDAIYAH - Mukti, Agus (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
Most of the concepts in science learning such as measurement, material change and phase substance are abstract ones. These concepts tend to be difficult to study by students who have not developed formal thinking ability. This difficulty may cause misconception, i.e. students’ conceptions which are different from those generally accepted by the scientific community. The sources of students’ misconception in learning science is text book used in the learning process, from students own self, and teachers' understanding of material presented to students.